Heliorhodopsin Evolution Is Driven by Photosensory Promiscuity in Monoderms - Bulzu, Paul-Adrian; Kavagutti, Vinicius Silva; Chiriac, Maria-Cecilia; Vavourakis, Charlotte D.; Inoue, Keiichi; Kandori, Hideki; Andrei, Adrian-Stefan; Ghai, Rohit (mSphere, 2021)
Heliorhodopsins are enigmatic, novel rhodopsins with a membrane orientation that is opposite to all known rhodopsins. However, their cellular and ecological functions are unknown, and even their taxonomic distribution remains a subject of debate. Rhodopsins are light-activated proteins displaying an enormous versatility of function as cation/anion pumps or sensing environmental stimuli and are widely distributed across all domains of life. Even with wide sequence divergence and uncertain evolutionary linkages between microbial (type 1) and animal (type 2) rhodopsins, the membrane orientation of the core structural scaffold of both was presumed universal. This was recently amended through the discovery of heliorhodopsins (HeRs; type 3), that, in contrast to known rhodopsins, display an inverted membrane topology and yet retain similarities in sequence, structure, and the light-activated response. While no ion-pumping activity has been demonstrated for HeRs and multiple crystal structures are available, fundamental questions regarding their cellular and ecological function or even their taxonomic distribution remain unresolved. Here, we investigated HeR function and distribution using genomic/metagenomic data with protein domain fusions, contextual genomic information, and gene coexpression analysis with strand-specific metatranscriptomics. We bring to resolution the debated monoderm/diderm occurrence patterns and show that HeRs are restricted to monoderms. Moreover, we provide compelling evidence that HeRs are a novel type of sensory rhodopsins linked to histidine kinases and other two-component system genes across phyla. In addition, we also describe two novel putative signal-transducing domains fused to some HeRs. We posit that HeRs likely function as generalized light-dependent switches involved in the mitigation of light-induced oxidative stress and metabolic circuitry regulation. Their role as sensory rhodopsins is corroborated by their photocycle dynamics and their presence/function in monoderms is likely connected to the higher sensitivity of these organisms to light-induced damage. IMPORTANCE Heliorhodopsins are enigmatic, novel rhodopsins with a membrane orientation that is opposite to all known rhodopsins. However, their cellular and ecological functions are unknown, and even their taxonomic distribution remains a subject of debate. We provide evidence that HeRs are a novel type of sensory rhodopsins linked to histidine kinases and other two-component system genes across phyla boundaries. In support of this, we also identify two novel putative signal transducing domains in HeRs that are fused with them. We also observe linkages of HeRs to genes involved in mitigation of light-induced oxidative stress and increased carbon and nitrogen metabolism. Finally, we synthesize these findings into a framework that connects HeRs with the cellular response to light in monoderms, activating light-induced oxidative stress defenses along with carbon/nitrogen metabolic circuitries. These findings are consistent with the evolutionary, taxonomic, structural, and genomic data available so far.